Application of behavioral economics for understanding health behaviors among adolescents and young adults. Issue 4 (5th August 2022) - Huynh, Ashley; Wisk, Lauren E.
Abstract : Purpose of review: Behavioral economics (BE) concepts have become well studied tools in addressing patient issues, such as weight loss, smoking cessation, and medication adherence. Although predominantly studied in adult populations, emerging literature has shown BE's utility for adolescent/young adult (AYA) populations, offering a practical framework to safeguard AYA health and influence healthy decision making. Recent findings: We identified substantive areas in which BE concepts have been applied in AYA populations (e.g., substance use) and outline how these concepts have been used as a tool to identify individuals at risk for poor outcomes and to leverage behavioral insights to improve health behaviors. Summary: BE research holds significant promise as a tool for clinicians and researchers to encourage healthy decision making in AYA populations. Yet, there are opportunities for BE research to expand further into current trends impacting adolescent health, such as electronic nicotine delivery systems, social media apps, and coronavirus disease 2019 vaccinations. Furthermore, the full degree of BE utility remains to be explored, as few studies demonstrate the translation of associative findings into direct interventions. Additional work is needed to formalize BE techniques into best practices that clinicians can implement in their daily practice.